An Empirical Analysis of Savings Determinants in Malaysia - Hafizah, Hammad Ahmad Khan (2009)
Saving is an important indicator of economic development where it is viewed as an element which finances domestic investment to achieve economic growth. The purpose of this paper is to examine the saving behavior in Malaysia. By using Life Cycle Model setting, this study employs a saving function which includes per capita income, rate of returns on savings deposit, government fiscal balance, young age dependency rate, old age dependency rate and also inflation rate as the potential determinants of saving. The empirical analysis is based on time series data for 30 years for period 1978 to 2007. The model tested for long run relationship using Johansen and Juselius multicointegration approach shows that per capita income, rate of returns, old age dependency and inflation rate are the determinants of national savings while per capita income, rate of returns, government fiscal balance, young age dependency, old age dependency and inflation rate are the determinants for private saving in a long run. On the other hand, results based on Vector Error Correction Model (VECM) show that per capita income, government fiscal balance and young age dependency are the significant determinants of national saving in a short run while private saving determinants are found to be per capita income, rate of return and young age dependency. Furthermore, variable ECM which indicates the speed of adjustment, shows that more than 75% of the adjustment is completed in a year for national saving determinants, while more than 86% of the adjustment is completed in a year for private saving determinants. Results obtain in this study suggest that policymakers should keep an eye on all of the significant variables since they give impact on savings rate.